Steady-state pharmacokinetics of galantamine are not affected by addition of memantine in healthy subjects - Yao, Caiping; Raoufinia, Arash; Gold, Michael; Nye, Jeffrey S; Ramael, Steven; Padmanabhan, Mukund; Walschap, Yolande; Verhaeghe, Tom; Zhao, Qinying (Journal of clinical pharmacology, 2005)
To evaluate the effect of multiple doses of memantine on the pharmacokinetics of galantamine and to assess the safety and tolerability of galantamine with adjunctive memantine treatment, an open-label, single-center, drug interaction study was conducted in 16 healthy adults. Subjects received an 8-mg dose of galantamine extended release once daily during week 1 and a 16-mg dose of galantamine extended release once daily during week 2. During weeks 3 and 4, they received a 16-mg dose of galantamine extended release once daily and a 10-mg dose of memantine twice daily, except on days 1 and 2 of week 3, when memantine was given as 10 mg once daily. The pharmacokinetic profile and parameters of galantamine at steady state were similar after administration of a 16-mg dose of galantamine once daily alone and after administration with a 10-mg dose of memantine twice daily. Galantamine 16 mg once daily with adjunctive memantine 10 mg twice daily was well tolerated and safe in healthy subjects.